Fully Transparent and High‐Performance ε‐Ga2O3 Photodetector Arrays for Solar‐Blind Imaging and Deep‐Ultraviolet Communication - Zhou, Shuren; Zhang, Hong; Peng, Xuan; Liu, Haowen; Li, Honglin; Xiong, Yuanqiang; Li, Wanjun; Yang, Ping-An; Ye, Lijuan; Kong, Chunyang (Advanced photonics research, 2022)
With the development of new broadband semiconductor materials and the expansion of solar‐blind deep‐ultraviolet (SBDU) optoelectronics, the demand for high‐performance fully transparent array integration has also increased. Herein, metal–semiconductor–metal (MSM)‐type fully transparent SBDU photodetector arrays (PDAs), based on commercially available ε‐Ga2O3 films, are constructed using indium tin oxide (ITO), indium gallium zinc oxide (IGZO), and aluminum zinc oxide (AZO) transparent conductive oxides as electrodes. The experimental results show that the overall performance of the fully transparent SBDU PDAs used in this study places them at the forefront of ε‐Ga2O3‐based photodetectors (PDs). All three PDs not only exhibit ultra‐high responsivity (286.2, 284.1, and 262.1 A W−1), remarkable detectivity (4.73 × 1014, 5.06 × 1014, and 2.16 × 1015 Jones), and excellent stability, but also fast photoresponse time (5.6/7.2, 6.9/9.5, and 70/200 ms). It is found that the resistivity and carrier concentration of transparent conductive oxides significantly influence device performance. Consequently, it is demonstrated, for the first time, that fully transparent ε‐Ga2O3‐based SBDU PDAs can be used as ultraviolet imagers and signal receivers integrated into a homemade solar‐blind ultraviolet communication (SBUC) system to transmit text data. These results indicate great potential for future applications of fully transparent ε‐Ga2O3 thin‐film solar‐blind photodetectors in next‐generation artificial intelligence eyes, smart windows, light field cameras, and solar‐blind imaging, among others. Fully transparent and high‐performance solar‐blind deep ultraviolet photodetector arrays (PDAs) based on ε‐Ga2O3 films are constructed with indium tin oxide (ITO), indium gallium zinc oxide (IGZO), and aluminum zinc oxide (AZO) transparent conductive oxides as electrodes. It is, for the first time, demonstrated that the fully transparent ε‐Ga2O3‐based PDAs can be used as an ultraviolet imager and signal receivers integrated into a homemade solar‐blind ultraviolet communication system for transmitting text data.